Advances in pulmonary neuroendocrine tumor management - Öberg, Kjell (Future Medicine Ltd (Unitec House, 2 Albert Place, London N3 1QB, UK), 2013)
Pulmonary neuroendocrine tumors (NETs) account for approximately one-quarter of all malignant lung cancers, the vast majority being represented by small-cell lung carcinoma. This thorough overview of this challenging field from international experts explores the various existing and emerging treatment options across the NET spectrum together with approaches to diagnosis and monitoring of disease.